Fatigue characteristics of continuous welded rails and the effect of residual stress on fatigue-ratchetting interaction. Issue 6 (16th March 2020) - Mansouri, Deniz; Sendur, Polat; Yapici, Guney Guven
ABSTRACT: The importance of ratchetting-fatigue interaction is garnering interest due to complex failure mechanism of rail welds under cyclic loading. The objective of this paper is to investigate the fatigue characteristics of continuous welded rails (CWRs) and the effect of residual stress on fatigue-ratchetting interaction. For this purpose, UIC60 rails have been modeled using a three-dimensional finite element model, including a combination of nonlinear kinematic and isotropic hardening. In addition, the interaction between cyclic loading and the effect of residual stress on fatigue is taken into consideration. Finite element model is validated against representative experimental findings. Smith–Watson–Topper (SWT) method is utilized in order to estimate the fatigue life of rail welds under static and cyclic loading. Lower fatigue life is predicted with increasing load due to the contact between rails and wheels. Simulation results also show that failure in the form of ratchetting occurs during the 10, 236th cycle, while failure corresponds to the 15, 290th cycle and the 145, 161st cycle based on the SWT and Coffin-Manson fatigue models, respectively. These findings suggest that investigations on ratchetting and fatigue should be carried out simultaneously to estimate the failure of the CWRs.